Pulmonary 3 T MRI with ultrashort TEs: Influence of ultrashort echo time interval on pulmonary functional and clinical stage assessments of smokers. Issue 4 (30th September 2013) - Ohno, Yoshiharu; Nishio, Mizuho; Koyama, Hisanobu; Yoshikawa, Takeshi; Matsumoto, Sumiaki; Seki, Shinichiro; Obara, Makoto; van, Marc; Takahashi, Masaya; Sugimura, Kazuro
<x xml:space="preserve">Abstract</x> Purpose To assess the influence of ultrashort TE (UTE) intervals on pulmonary magnetic resonance imaging (MRI) with UTEs (UTE‐MRI) for pulmonary functional loss assessment and clinical stage classification of smokers. Materials and Methods A total 60 consecutive smokers (43 men and 17 women; mean age 70 years) with and without COPD underwent thin‐section multidetector row computed tomography (MDCT), UTE‐MRI, and pulmonary functional measurements. For each smoker, UTE‐MRI was performed with three different UTE intervals (UTE‐MRI A: 0.5 msec, UTE‐MRI B: 1.0 msec, UTE‐MRI C: 1.5 msec). By using the GOLD guidelines, the subjects were classified as: "smokers without COPD, " "mild COPD, " "moderate COPD, " and "severe or very severe COPD." Then the mean T2* value from each UTE‐MRI and CT‐based functional lung volume (FLV) were correlated with pulmonary function test. Finally, Fisher's PLSD test was used to evaluate differences in each index among the four clinical stages. Results Each index correlated significantly with pulmonary function test results (P < 0.05). CT‐based FLV and mean T2* values obtained from UTE‐MRI A and B showed significant differences among all groups except between "smokers without COPD" and "mild COPD" groups (P < 0.05). Conclusion UTE‐MRI has a potential for management of smokers and the UTE interval is suggested as an important parameter in this setting. J. Magn. Reson. Imaging 2014;39:988–997. © 2013 Wiley Periodicals, Inc.